The state of the marine report environment for Australia. - Zann, Leon P.; Kailola, Patricia (Canberra, Australia Great Barrier Reef Marine Park Authority, 1995)
Technical annex 1: The marine environment
Keywords: Marine pollution; Marine resources; Marine resources